TEACHING CHILDREN TO THINK IN SPEECH DEVELOPMENT CLASSES OF PRESCHOOL EDUCATIONAL INSTITUTIONS - Abdurakhmatova Miyassar (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
The article deals with some issues of teaching children to think independently through didactic games in speech development classes in preschool education, and expresses theoretical views.